2020
DOI: 10.1002/jmv.26277
|View full text |Cite
|
Sign up to set email alerts
|

First molecular characterization of the hepatitis E virus in humans in Cameroon: Confirmation of the HEV outbreak in Touboro, North‐Cameroon

Abstract: Hepatitis E virus (HEV) is a major causative agent of acute viral hepatitis in many regions of the world including Africa. In Cameroon, there is no published molecular study on HEV in humans. However, based on serological assays, the first outbreak of HEV was detected in North‐Cameroon. The objective of this study was to determine the molecular characterization of HEV that circulated during this period. A retrospective study design was used to select serum samples among those collected during the outbreak peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(41 reference statements)
3
6
0
Order By: Relevance
“…Molecular analysis of HEV strains, obtained from infected patients, revealed that genotype 1e was the source of contamination during this epidemic. These results from our phylogenetic analysis are consistent with previous findings regarding the subtypes circulating in the CAR [ 22 , 31 ] and neighboring countries [ 32 , 33 ], and with waterborne transmission usually associated with HEV genotypes 1 and 2. Our genotypes 1e strains formed a cluster which were close to those found in the country during the 2008–2009 outbreak and in neighboring countries [ 22 , 32 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Molecular analysis of HEV strains, obtained from infected patients, revealed that genotype 1e was the source of contamination during this epidemic. These results from our phylogenetic analysis are consistent with previous findings regarding the subtypes circulating in the CAR [ 22 , 31 ] and neighboring countries [ 32 , 33 ], and with waterborne transmission usually associated with HEV genotypes 1 and 2. Our genotypes 1e strains formed a cluster which were close to those found in the country during the 2008–2009 outbreak and in neighboring countries [ 22 , 32 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results from our phylogenetic analysis are consistent with previous findings regarding the subtypes circulating in the CAR [ 22 , 31 ] and neighboring countries [ 32 , 33 ], and with waterborne transmission usually associated with HEV genotypes 1 and 2. Our genotypes 1e strains formed a cluster which were close to those found in the country during the 2008–2009 outbreak and in neighboring countries [ 22 , 32 , 34 ]. Our results show that HEV evolves very little and has circulated endemically in this area for almost 15 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study reports for the second time the detection and characterization of HEV RNA in humans in Cameroon. HEV RNA was first detected and characterized in 2020 in a retrospective study that confirmed serological data from the first HEV outbreak which occurred in 2013 [ 11 ]. Two HEV genotypes circulating during this outbreak were identified, namely genotypes 1 (subtype 1e) and 3 (subtype 3f).…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, the disease was initially suspected by local health authorities to be a yellow fever (YF) outbreak due to the predominance of jaundice. However, laboratory analysis ruled out yellow fever and identified HEV in 90% of cases, with genotypes 1, 2 and 3 present [ 10 , 11 ]. Since this outbreak, no other HEV outbreak has been reported in the country and little is known about the prevalence and genetic diversity of the HEV among symptomatic patients in Cameroon.…”
Section: Introductionmentioning
confidence: 99%